Late Holocene Sedimentation and Environmental Change Record in Billefjorden, Svalbard - Szczuciński, Witold (My University, 2004)
The Late Holocene sedimentation in Billefjorden (Svalbard) was studied through investigations of modern sedimentation conditions and their effects recorded in sediments. Sedimentation in the fjord is dominated by settling from surface turbid water plumes originating from rivers and subglacial outflows of tidewater glacier. Sedimentation is confined to the summer season (July - August) and is largely influenced by flocculation. It results in high particulate matter fluxes (up to 100 g m-2 day-1), poorly sorted sediments, and trapping of most of the sediments in the proximal few hundred meters (in case of rivers ending on tidal flats – flocculation occurs on tidal flat) to a couple of km in the case of tidewater glacier (flocculation happens after reaching the fjord waters). In the fall season, sedimentation rates are much smaller – mainly due to a smaller sediment supply but also in the effect of a largely diminished flocculation process. The latter one was found to be controlled primarily by the mixing of fresh and saline waters (so by freshwater inflow) and not by SPM concentrations. Sediment accumulation rates decrease exponentially from the source with more than 4 cm per year in the proximal settings to about 0.1 cm y-1 in the central basin. Sedimentation from icebergs has at least one order of magnitude lower rates. Fjord bottom sediments are mostly muds with bimodal grain size distribution (due to at least two sedimentation processes: suspension settling and iceberg rafting). Differences in their chemical (major, trace elements, and REE) mineralogical and coarse grain fraction composition are small but distinct. The deposits can be divided into regions supplied by local sources (e.g. Adolfbukta, Petuniabukta, Mimerbukta, central basin, entrance sill), supporting the conclusion of sediment trapping in proximal settings. The influence of rafted sediments is visible – especially in central basin sediments because the bulk of them is supplied from catchments of different geology. In the studied cores, early diagenesis is exemplified by compaction, small sediment mixing (through bioturbation and physical processes), and chemical processes associated with the redox zone. The most spectacular one is shown by the dissolution of benthic agglutinated foraminifera cement and their sharp decline in the upper few cm of sediment cores. A study of the multiproxy signal revealed several changes associated with environmental as well as anthropogenic changes. The most striking are changes in sediment accumulation rates in the fjord central basin. In the period 1300 AD to about 1895 (maximum extent of LIA glaciers), the rates were at least one order of magnitude lower than after LIA. The latter is also the highest in the whole Holocene period. Smaller fluctuations were also associated with tidewater proximal cores where they decrease with increasing distance from the sediment source (glacier retreat). An unusual situation was observed in the core located in the vicinity of Pyramiden (coal mine and settlement active between 1945 and 1998) where in the 50s sediment accumulation rates were elevated possibly in association with earthworks in the settlement and in the mining area. The sediment chemical composition also changed through time – the most distinct change happened around the 1950s, when in the central basin cores increased the relative ratio between carbonate-related elements (local catchments) and silica and aluminosilicate-related elements (partly controlled by input from icebergs). It well correlates with tidewater glacier retreat into the shallower water area and consequently decreasing iceberg production. One of the most striking changes in the sediments associated with anthropogenic activity is significantly elevated coal sand and dust content in the sediments, which concentrations well correlates with the intensity of coal mining in the Pyramiden. In light of projected future climatic changes in this part of the Arctic, the main changes are expected in sediment budget. With increasing freshwater (due to increasing precipitation and ablation) and consequently in sediment delivery, the average sediment accumulation rate will increase. However, it will be even more concentrated in proximal settings (prolonged and intensified conditions for the flocculation process). The input of deposition from icebergs will be likely smaller since the only tidewater glacier is retreating into a more and more shallow setting. Parts of the thesis were published as: Szczuciński, W., Zajączkowski, M., 2012 – Factors controlling downward fluxes of particulate matter in glacier-contact and non-glacier contact settings in a subpolar fjord (Billefjorden, Svalbard). Sediments, Morphology and Sedimentary Processes on Continental Shelves: Advances in technologies, research and applications (Special Publication 44 of the IAS), Li M., Sherwood C., Hill P. (eds). Wiley-Blackwell Publishing, 369-386. (https://onlinelibrary.wiley.com/doi/10.1002/9781118311172.ch18) Szczuciński, W., Zajączkowski, M., Scholten, J., 2009 – Sediment accumulation rates in subpolar fjords – impact of post-Little Ice Age glaciers retreat, Billefjorden, Svalbard. Estuarine, Coastal and Shelf Science 85(3): 345-356. (https://www.sciencedirect.com/science/article/abs/pii/S0272771409004193)
Późnoholoceńska sedymentacja i zapis zmian środowiskowych w osadach Billefjorden, Svalbard
Keywords: Spitsbergen; Svalbard; Billefjorden; Petuniabukta; Adolfsbukta; Nordenskioldbreen; Fjord; Sediments; Marine sediments; Fjord sediments; Sediment geochemistry; Arctic; Pyramiden; Sedimentation; Glacimarine sedimentation; Meltwater river; Glacial bay; Glaciers; Glaciomarine; Sediment provenance; Sediment traps; Sedimentation rate; Sediment accumulation rate; Flocculation; Hydrography; Oceanography; particulate matter flux; seasonal changes; suspended sediment; suspended particulate matter; sediment cores; Holocene; dating; radiocarbon; 210Pb; 137Cs; accumulation rate; ice rafted debris; coal; anthropogenic impact; environmental changes; XRD; tidewater glacier; tidal flat; sedimentary record; mud; grain size; REE; lead-210; caesium-137; iceberg; sediment discharge; sediment supply; Little Ice Age; XX century